Extraction of residual oil from oil palm decanter cake by using mini-pilot soxhlet system and its management recommendations / Nurul Haziqah Shaharuddin - Shaharuddin, Nurul Haziqah (Faculty of Plantation and Agrotechnology, 2018)
Elaeis guineensis or also commonly known as oil palm tree was originated came from West Africa where fIrstly they were live wildly. Decanter cake are produced after the pressing of sludge that has been collected from oil storage. Decanter cake usually returning back to fIeld as a fertilizer for the palm tree. But as a concern of the environment, there are still small amount of oil left in the decanter cake as it can cause inhabitation of the microorganism activities since residual oil can't be easily decomposed by microorganism. This study was about to discover how much residual oil left in decanter cake by using Mini-Pilot Soxhlet System with aid of hexane as the solvent to extract the residual oil. Residual oil were extracted after few cycles of extraction process. The sample used this study is dry basis sample or wet basis sample. The result of oil extracted from dry basis sample were 5 times higher than wet basis sample. This is because the moisture of sample affect the oil extraction experiment. Since there are 10% of oil content within the decanter cake, over RM99.45/ton oil yield has lost. It is more economic if supplier of decanter extract residual oil fully from the solid.